Propagation loss on a Si-Slab Waveguide: Simulation revisited - Wildan Panji Tresna; Takeo Maruyama (Journal of Physics and Its Applications, 2019)
Slab waveguide is one of the simplest types of optical waveguide, the confinement factor is only determined by the thickness of one side so that the propagation of light passing through it will be confined in the material. The slab waveguide is built from Si as the core material and SiO2 as the substrate. The use of various optical waveguides is very dependent on the objectives to be achieved in its application, for it is very important to know the characteristics of each optical waveguide. In this paper the writer wants to know the characteristics of a slab waveguide, specifically with regard to propagation loss. The simulation results show that the propagation loss in the slab waveguide design that the authors propose is around 0.1dB / mm in TE mode conditions. The occurrence of propagation loss in the simulation is likely due to imperfections in determining the effective material index in the design of the slab waveguide.